A summation-integral type modification of Szasz-Mirakjan-Stancu operators - Mishra, Vishnu Narayan; Gandhi, Rajiv B.; Mohapatra, Ram N. (J. Numer. Anal. Approx. Theory, 2016)
In this paper we introduce a summation-integral type modification of Szasz-Mirakjan-Stancu operators. Calculation of moments, density theorem, a direct result and a Voronovskaja-type result are obtained for the operators.